CONSIDERATIONS REGARDING ORTHODONTIC TREATMENT IN ADULT PATIENTS WITH EXTRACTION OF ECTOPIC CANINES - Mioara Decusara; Dorina-Cerasella Şincar; Cristian Constantin Budacu; Oana Chipirliu; Gabriela Popa; Gabriel-Valeriu Popa; Gabi Topor; Kamel Earar (Romanian Society of Oral Rehabilitation, 2019)
Orthodontic treatment aims to give patients a more satisfactory dental and facial appearance and to improve the functions of the dentomaxillary apparatus. Orthodontic treatment is influenced by the pattern of facial growth, the development of dentition and occlusion, and the severity of the dento-maxillary abnormality. Patients often require orthodontic treatment for dental crowding, especially in the anterior dental area. Following the clinical examination and study models, the radiological examination (orthopantomogram and cephalography) and after establishing the orthodontic diagnosis and prognosis, the orthodontist may recommend performing dental extractions to achieve dental alignment and stable occlusal relationships, with maximum intercuspidation. Depending on the clinical situation and the severity of the dento-maxillary abnormality, is recommended extraction of the premolars, the wisdom molars , the teeth affected by carious lesions, with large and irreparable coronary destruction. The indication of definitive canine extraction should be avoided in view of their coronadicular anatomy and the importance of facial aesthetics and mandibular functional movements. In this article we will present orthodontic treatment in one case of adult patient who have requested dental alignment and occlusal balancing after definitive canine extractions. The extractions were carried out in childhood by dentists, dued to the canine vestibular ectopic position, the dental crowding, without subsequent orthodontic treatment.